Inflasi, Perdagangan Internasional, dan Kapitalisasi Saham Syariah sebagai Determinan Pertumbuhan Ekonomi Indonesia Periode 2011–2025 - Yuni Asri; Datien Eriska Utami (Jurnal Ilmiah Ekonomi Islam, 2026)
Economic growth is a key indicator of a country’s development success and reflects the economy’s ability to improve the welfare of its people in a sustainable manner. Various macroeconomic and financial factors play a role in determining the dynamics of economic growth, including inflation, international trade, and the development of the Islamic capital market. This study analyzes the effects of inflation, international trade, and Islamic stock market capitalization on Indonesia’s economic growth from 2011 to 2025, incorporating exchange rates and interest rates as control variables. The study employs a quantitative approach using monthly time-series data from January 2011 to December 2025 obtained from the Central Statistics Agency, Bank Indonesia, and the Financial Services Authority. The analysis was conducted using the Autoregressive Distributed Lag (ARDL) model, as it is capable of identifying both short-run and long-run relationships among the variables. The results indicate that all variables exhibit long-run cointegration. In the long-run estimation, inflation has a negative and significant effect on economic growth, while sharia stock market capitalization has a positive and significant effect on economic growth. International trade shows no significant effect in the long run. In short-run estimates, international trade has a significant negative effect at several lag periods, while the exchange rate, as a control variable, shows a significant effect on economic growth. Interest rates have a significant negative effect in the long run but no significant effect in the short run. The research findings underscore the importance of price stability and the strengthening of the Islamic capital market in driving sustainable economic growth in Indonesia. Furthermore, the use of the exchange rate and interest rates as control variables enhances the model’s reliability in explaining the dynamics of Indonesia’s economic growth.